Adverse Childhood Experiences and Adulthood Negotiation in Intimate Partner Violence: The Sequentially Paradoxical Role of Interpersonal Sensitivity Among Female Inmates - Johns, Lance (Journal of interpersonal violence, 2021)
The present study examined interpersonal sensitivity and hostility as separate and sequential mediators in the association between adverse childhood experiences (ACE) and the conflict tactic of negotiation (e.g., a strategy utilized to resolve conflict with a romantic partner) among female inmates. Participants were 258 female inmates recruited from three Southern California jails. After statistically controlling for partner-negotiation, results from a sequential mediation model revealed that the association between ACE and negotiation was mediated through three separate pathways. The first single mediational pathway indicated that ACE was positively associated with interpersonal sensitivity, which in turn had a positive association with negotiation. The second single mediational pathway revealed that ACE was positively associated with hostility, which in turn had a negative association with negotiation. Finally, the sequential meditational path revealed that interpersonal sensitivity through hostility mediated the ACE and negotiation relationship. The present results suggest that ACE may result in increased interpersonal sensitivity, which may paradoxically result in both more and less negotiation with romantic partners. That is, ACE through interpersonal sensitivity alone may result in more negotiation, and ACE through interpersonal sensitivity and then hostility may result in less negotiation with romantic partners. We explicate how the psychopathological construct of interpersonal sensitivity may lead to increased and decreased rates of the positively construed conflict tacit of negotiation. In addition, the present findings are discussed in light of the high rates of both revictimization and perpetration of violence among female inmates.